Thyroid ophthalmopathy in an adolescent girl: a case report - Devi, Bhanu; Das, Rajiv Kumar; Phukan, Shobhana (International Journal of Research in Medical Sciences, 2017)
A 14 year old girl presented with protrusion of both the eyes for duration of 3 months and pain, redness and watering of right eye for 20 days. On examination, she was thin built, poorly nourished and the thyroid gland was found to be enlarged. Both eyes were proptosed and there was incapability of complete closure of the eyelids on both sides. On right eye, conjunctiva was congested and there was a corneal lesion seen inferomedially with an epithelial defect. CT scan of the orbit revealed picture of thyroid ophthalmopathy. Thyroid profile revealed picture suggestive of hyperthyroidism and anti-thyroid peroxidase antibody was found to be very high. She was diagnosed as a case of thyroid ophthalmopathy both eyes with exposure keratitis right eye. She was treated with anti-thyroid medication along with conservative treatment for ocular symptoms and lateral tarsorrhaphy of right eye for exposure keratopathy. Pulse steroid therapy was started and subsequent follow up showed resolution of the signs.